Culprit or Accomplice: Observations on the Role and Perception of Music in Violent Contexts in the Sierra Leone War - Cornelia Nuxoll (Transposition)
The article focuses on the role of music among RUF combatants fighting in the Sierra Leone civil war. It touches on some widely held notions of music and a general reluctance towards the idea that music can be instrumentalised for violent means. Furthermore, it will address in what way the research focus on music was conducive to qualitative interview sessions and direct interactions with former RUF members. Special focus lies on the songs that inspired rebel fighters and how these songs were used to prepare for and accompany violent attacks. The article concludes by exploring and comparing how perpetrators, victims and musicians assess the appropriation of music in the context of violence and how they feel about the songs today.